The Effect Of “Think-Aloud” Strategy On Students’ Inferential Reading Comprehension - Dina Irmayanti Harahap; Rahayu Syafitri (Universitas Potensi Utama, 2022)
There are four skills in English, namely speaking, writing, reading, and listening. One of those skills is reading which perceived a written text in order to understand its contents. To understand the contents of the text, the students faced many problems. Some of them don’t understand about the meaning of the words and lack in vocabularies and some of them think that reading is boring activity. This condition and situation caused some of the students feel bored when they joint in the reading class. In this research, the researcher was aimed to find out the effect of think-aloud strategy in teaching inferential reading comprehension at a vocational school SMK PELAYARAN SAMUDERA INDONESIA MEDAN in academic year 2021/2022. The method of this research is an experimental research. The researcher took data from the eleven (XI) grade students of nautical class A and B as the sample of the research. The nautical class A as experimental group and the nautical class B as control group. Each class consists of 30 students. Dealing with the research instrument of collecting the data, the researcher used a test which consisteds of pre-test and post-test and conducted before and after treatment. To analyze the data, the researcher applied the t-test. The result of this research showed that the students mean scores in reading comprehension who were taught by think-aloud strategy is higher, while the students mean scores in reading comprehension who were taught by the Group Discussion strategy is lower. The result of t-test computation pointed that tobservation is high while the value ttable is low . It shows that tobservation is higher than ttable ( to>tt). Therefore the alternative Hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. In other word, it can be concluded that think-aloud strategy is effective to to increase the students inferential reading comprehension of students at SMK PELAYARAN SAMUDERA INDONESIA Medan.